Czy angielski zastąpił (w Polsce) łacinę? Kilka uwag o kwestii językowej na kanwie "Nowel i opowiadań" Henryka Sienkiewicza - Wicher, Andrzej (Er(r)go. Teoria - Literatura - Kultura, 2011)
The aim of the essay is to consider the ramifications of abandoning Latin as the lingua franca of Europe (with primary emphasis on Poland) and embracing English as a new international standard of communication. In Poland the use of foreign languages has always been fraught with political and class implications. At the same time certain foreign languages (e.g. Latin, French) have been used to bestow distinction on the speaker/writer and identify her/him as a superior citizen. In Sienkiewicz’s novellas and short stories, characters resort to various foreign languages to convey their attitudes to particular nations and emphasize their social positions.